Reading understanding and the reading speed in sixth grade students of primary of public and private schools of metropolitan area of Lima-Perú - Escurra-Mayaute, Luis Miguel (2003)
The study allowed the analysis of the relationship that exists between reading understanding and reading comprehension and reading speed among sixth grade students in the Metropolitan Area of Lima. The study used a probabilistic sample of 541 students, 402 came from public schools and 109 from private schools, 272 were boys and 269 girls, between 11 to 13 years of age. The reading speed test presented validity and reliability.. The comparisons indicated that students from private schools presented better levels of reading comprehension and of reading speed and a greater relationship between reading comprehension and reading speed than that of students from public schools.